2020
DOI: 10.18502/ijps.v15i1.2440
|View full text |Cite
|
Sign up to set email alerts
|

Association of Internet Addiction with Emotional and Behavioral Characteristics of Adolescents

Abstract: Objective: This study aimed to measure the prevalence of internet addiction and its impact on the psychological well-being of adolescents in Tehran, considering the sociodemographic characteristics. Method: In this cross sectional study, a total of 945 (mean age of 14.85) students (522 boys and 423 girls) were recruited by 2-stage clustering sampling method in 2017. The Chen Internet Addiction Scale (CIAS) and Youth Self-Report (YSR) were used to measure internet addiction and psychological characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 33 publications
1
6
0
3
Order By: Relevance
“…Our findings showed that internalization and externalization problems were correlated to higher KDAI scores. This finding corresponded with other studies about this issue on adolescents ( 53 55 ). Our previous study before the COVID-19 pandemic on adolescence also showed a similar result ( 56 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings showed that internalization and externalization problems were correlated to higher KDAI scores. This finding corresponded with other studies about this issue on adolescents ( 53 55 ). Our previous study before the COVID-19 pandemic on adolescence also showed a similar result ( 56 ).…”
Section: Discussionsupporting
confidence: 93%
“…Our previous study before the COVID-19 pandemic on adolescence also showed a similar result ( 56 ). However, most studies were cross-sectional, which could not explain causality between internalization/externalization problems and IA ( 53 , 55 ). A longitudinal study showed that internalization or externalization problems might contribute as risk factors for IA ( 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in our study, girls' excessive use of social media had often caused depression, stress, anxiety, and severe psychological and intellectual dependence on social media. Previous studies also showed that girls spend more time on social networks and this can lead to symptoms of depression, stress and anxiety and dependence [ 13 , 14 , 19 , 20 , 62 ]. In addition, similar to previous research, our results suggest that specific smartphone apps, including calls and instant messaging, help increase feelings of dependency.…”
Section: Discussionmentioning
confidence: 99%
“…As social media use is rising among adolescents, the benefits and drawbacks of this use on adolescent development and health status are areas of concern [ 3 , 11 , 12 ]. It has been demonstrated in recent research that increasing social media use is one important factor affecting adolescents' mental health, and that social media use may have more adverse psychological impact on girls than on boys [ 7 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with other maladaptive problems, Internet addiction is strongly correlated with anxiety and depression ( Li et al, 2019 ; Andrade et al, 2020 ). Emotional problems, of which depression and anxiety are the most common ( Tsai et al, 2020 ), and the comorbidity rate is high ( Zeng et al, 2019 ), can mediate other psychological and behavioral problems ( Warren et al, 2021 ); moreover, difficulty in emotional regulation can predict subsequent Internet addiction ( Effatpanah et al, 2020 ). Among college students, emotional problems are more common, particularly depression and anxiety ( Ramón-Arbués et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%